Redemption, settlement and agriculture in the religious teachings of Hovevei Zion - Mashiach, Amir (HTS teologiese studies, 2021)
Hovevei Zion is a collective name for several societies established in Eastern Europe in the 19th century, advocating immigration to the land of Israel, settlement of the land and agricultural work. This article examines the religious approach of several prominent thinkers from among Hovevei Zion and the First Aliya, who shared the perception of farming and settling the land as having religious and even messianic meaning. It was clear to them that the Torah is the foundation of the Jewish people’s existence, however, to this they added another value – work. These thinkers strived to change the identity of the exilic Jew, who was occupied only with spiritual religious life and to reinstate the identity of the biblical Jew, who combined a spiritual and a material religious life. The article examines the approach of Hovevei Zion in light of the general rabbinic approach to redemption, settlement and agriculture and the social changes in 19th century Europe.Contribution: This article contributes to the journal’s multidisciplinary theological perspective, particularly the notion ‘historical thought’, which covers the textual and oral history and hermeneutical studies, narratives and philosophies behind the Abrahamic religions as expressed in the Hebrew Scriptures and the Rabbinic literature.